BETWEEN PRECISION AND VAGUENESS – THE PROBLEMS OF TRANSLATION OF GERMAN AND POLISH LEGAL VAGUE TERMS - KĘSICKA, Karolina (Comparative Legilinguistics, 2014)
The paper tries to outline the characteristics of vague legal terms and the problem of their translation. At the beginning of the article, the author points out some reasons for semantic indeterminacy in technical terminology, with particular focus on the language of the law. The discussion of examples is followed by the presentation of some theoretical issues related to vague legal terms. On that basis, the author presents examples of vague legal concepts and terms in the German and Polish civil law and analyses ways to handle translation problems with the assistance of legal interpretation and comparative law which were proposed in the translated legal texts and bilingual legal dictionaries. The applied analysis model based on the rules of comparative legal analysis will be made on the basis of the following steps: semantic analysis of the legal concepts defined in the source legal system, comparative legal analysis with a view to similarities/differences concerning the interpretation of the legal concepts in both legal systems and the analysis of terminological equivalence of translation into the target language.